Mental Distress in Patients with Cerebral Visual Injury Assessed with the German Brief Symptom Inventory - Gall, Carolin; Brösel, Doreen; Franke, Gabriele Helga (Frontiers in Aging Neuroscience, 2015)
Background While there are reports on vision-related quality of life in patients with vision impairment caused by both ophthalmic and brain diseases, little is known about mental distress. In fact, mental distress after cerebral visual injury has been widely ignored. Methods Mental health symptoms were assessed in 122 participants with visual field defects after brain damage (72 male, mean age 58.1 ± 15.6 years), who completed the German Brief Symptom Inventory (BSI) at their homes after they had been asked by phone for their participation. Results Clinically relevant mental distress was present in 25.4% of participants with cerebral visual injury. In case of multisensory impairment, an increased amount and intensity of mental distress symptoms was observed compared to the subsample with only visual impairment. Conclusion Assessment of comorbid mental health symptoms appears to be clinically meaningful in brain-damaged patients with visual sensory impairment. In case of clinically relevant mental distress, psychological supportive therapies are advisable especially in subjects with cerebral visual injury and comorbidities affecting other sensory modalities as well.